INFLUENCE OF RECESS ON PUPIL’S ACADEMIC PERFORMANCE IN AWKA SOUTH LOCAL GOVERNMENT EDUCATION AUTHORITY - Enemuo, J. O; Anselem, Ebele Amala (Journal of Early Childhood and Primary Education, 2025)
This study determined the influence of recess on pupil’s academic performance in Awka South Local Government Education Authority. Two purpose and two research questions guided the study. The population for the study comprises 927 basic school teachers in 45 basic schools in Awka South Local Government Education Authority, in Anambra State. The sample for this study comprised 125 primary school teachers drawn from the sampled 25 basic schools in Awka South Local Government Education Authority. This represents approximately 13.5 percent of the entire population. Using the simple random sampling technique of balloting with replacement, 5 teachers in public basic schools were selected from each of the sampled basic schools in Awka South Local Government Education Authority. The instrument for data collection was a 14 item self-structured questionnaire. The instrument was face and content validated by three experts, one in the Department of Educational Foundations and two from the Department of Early Childhood and Primary Education all from the Faculty of Education in Nnamdi Azikiwe University, Awka. The internal consistency of the questionnaire was established using the Cronbach alpha method and yielded coefficient values of 0.64 and 0.71 for sections A and B. Questionnaires were administered personally by the researcher with the help of two (2) research assistants. Data collected for this study was analyzed using mean and standard deviation for research questions. The findings of the study revealed that the respondents rated strongly agreed to the items raised on the influence of recess on pupil’s academic performance in Arithmetic in Awka South Local Government Education Authority; the study further reported that the respondents rated agreed to the items raised on the influence of recess on pupil’s academic performance in reading comprehension in Awka South Local Government Education Authority. Conclusion was made and it was recommended that State Ministry of Education should ensure that adequate play facilities are provided, before granting approval to schools among others.